Gomo Toma Game Media as a Means to Improve Understanding of Multiplication Concepts in Mathematics Subjects in Class IIA Students of Ende 3 SDK Ende Regency - Chatarina Novianti; Yuliani Sepe Wangge (Universitas Muhammadiyah Enrekang, 2022)
The selection of Gomo Toma game media in learning Mathematics is as follows. First, the Gomo Toma game media is a game that is very close to children's lives and is played by children. Second, it is hoped that the Gomo Toma game media can improve the understanding of mathematics concepts for class IIA students in learning mathematics, this is because elementary school students still like to play, so the game approach will be more effective. Third, in the Gomo Tomo game there are competitive, cooperative, and entertainment values. Fourth, there are many positive sides contained in the snake and ladder game, including training in psychomotor development, cognitive, communicative balance so that it is beneficial for the mental development of elementary school age children. 7-12 years This is supported by the opinion of several experts who state how important games are for children. According to Ljublinskaja Games are a reflection of reality, as an initial form of acquiring knowledge. This is also reinforced by Freeman which states that in general, experts agree that playing is an activity that helps children achieve complete development, both physically, intellectually, socially, morally and emotionally. Rofi'uddin states that the use of forms of games in learning will provide a pleasant climate for students, so that the learning process of students is carried out without coercion, but instead with a sense of harmony. In addition, by playing, students can learn in a relaxed manner. In a relaxed way, students' brain cells can develop, which in the end students can absorb information and get a deep impression of the subject matter. Subject matter can be stored continuously in long-term memory.